Smart Grid District Heating Business Model – Smart Energy Management from a Customer and End User Perspective: A case study of smart grid District Heating Business Development in Malmö, Hyllie - Tsai,Yung-Wei; Baldvinsson,Gísli Páll; Solomentsev,Gleb; Zhang,Lin (2012)
Background: The current mass proliferation of information and communication technology (“ICT”) has created the ability to communicate with customers and manage energy production in unprecedented ways. With the arrival of “smart” energy meters and wireless communication, a new level of customer interaction is possible. In this scenario, a “smart grid” is created in which multiple energy meters are interconnected throughout the energy network. The constant communication and feedback made possible by this technology, allow for demand side management (“DSM”) of energy production, where users at the point of consumption, can set their own usage according to their requirements and the production source can meet the demand as the system requires it. The evolution of this system is still unclear however and how the new energy “products” and energy business will look like is unknown. To test potential variants of this smart system, energy supplier E.ON is testing variants of the system in a local ‘green-field’ development project, Hyllie, in Malmö Sweden. This report looks at the incentives and barriers for the adoption of such a system in the Hyllie development from a company and customer perspective. The focus of the project is on E.ON Värme, a daughter company of E.ON Nordic. Purpose: The purpose of this study is to gain an understanding the customer and end users incentives and preferences of E.ON Värme’s major customers to implement smart grid district heating. Based on these aspects in the foreground, the authors will further develop a matrix of drivers and barriers for smart grid implementation from E.ON Värme’s business perspective, customer perspective and end-user perspective. The final deliverable will be feasible business models with new customer segmentations proposed by the authors. Method: This study required a mix of quantitative and qualitative data and in gathering that data a variety of methods were used. Interviews with E.ON personnel and customers were conducted in a semi-structured manner and an online end-user survey was carried out to develop an understanding of the end-user. The findings from these methods were supported with existing literature. A workshop with E.ON personnel was carried out to validate the authors’ data analysis. Conclusions: The authors find that the current district heating grid has not yet adapted to smart metering technology. The current business model is limited in in its capacity to meet all the challenges faced in a changing energy industry. The current segmentation does not accurately capture the needs and preferences of the new energy consumer, and cannot fully connect customer incentives, to end-user behaviors. The authors have proposed a new customer segmentation and consequently five different business models focusing on different needs of each segment which can help E.ON Värme to meet future challenges.
Keywords: E.ON Värme; District Heating; Smart Grid; Energy Management; Customer and End-User incentives and Preferences; Customer Segmentation; Business Model Canvas; Peak Load Problems.